The Use of Translation Techniques in Translating Sarcasm in the English-Indonesian Translation of Dialogues in Mean Girls (2004) - Rahayu, Santi; Thohiriyah, Thohiriyah (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This study aims to analyze how sarcasm is translated in the Indonesian subtitles of the film Mean Girls (2004), focusing on the official version available on HBO. Sarcasm, as a form of expression that relies heavily on context, tone, and cultural understanding, presents particular challenges in the translation process. Specifically, this research seeks to identify the various types of sarcasm appearing in the film and to evaluate the translation methods used to represent these sarcastic expressions in the target language. The method employed is a qualitative descriptive approach. Data were collected by identifying and categorizing sarcastic utterances within the film. Subsequently, the data were analyzed using the translation techniques framework by (Nuriah & Khoirunnisa, 2024) to classify the applied translation methods. The analysis involved an in-depth examination of the utterances’ contexts and a comparison between the source text and its translation. The findings reveal that literal translation is the most frequently used technique, accounting for 56.8%, followed by reduction (16.2%), generalization (8.1%), and discursive creation (8.1%). Other techniques such as modulation, amplification, equivalence, and borrowing were each applied 2.7% of the time to address specific challenges like ambiguity and idiomatic expressions. While literal translation tends to maintain formal equivalence between the source text and the translation, it often fails to fully convey the sarcastic meaning, resulting in a loss of nuance and humor. Conversely, more creative and context-sensitive techniques, although used less frequently, prove to be more effective in preserving the pragmatic force of sarcasm. This study concludes that successful sarcasm translation largely depends on the translator’s creativity and awareness of linguistic and cultural differences.